Analysis and assessment of emerging countries’ experience in local development strategy The case of Turkey for the period 2002-2015 - nassire, ahmed (Milev Journal of Research and Studies, 2016)
This study seeks to shed light on the analysis and evaluation of local development strategy experience in emerging countries through the Turkish experience in the light of the political and economic changes taking place in the country since 2002, which led to achieve the longest period of economic boom in the history of Turkey, foreign investment have been doubled according to what they used to be, with more than four hundred billion dollars since 2002 - this is much more than what was invested in the last sixty years, in addition to that, per capita income grew to about twelve-thousand US dollars to be tripled from what it was before. Moreover, various achievements have been realized in the infrastructure, such as highway incision and bridge construction, and the provision of electricity and running water, the unemployment and inflation have been reduced and the legal health insurance has been adopted; all actions benefiting in particular categories uneducated and low-incom